MENINGKATKAN LITERASI DIGITAL DAN OPTIMALKAN PEMANFAATAN KOMPUTER MELALUI DIGITALISASI LAYANAN PEMERINTAHAN DESA KOTA CIREBON - Permana, Indra Surya Permana; Ngiliyun, Ahmad Ngiliyun (Aspirasi Masyarakat, 2025)
This community service activity aims to improve digital literacy and optimize the use of computers in administrative services in Klayan Village, Cirebon City. The implementation of the activity was carried out from March to April 2025 through a participatory approach, direct training, and field assistance. Training materials include the use of basic computers, Microsoft Office, and an introduction to digital-based village information systems. The evaluation of the activity showed a significant increase in participant skills, with post-test scores higher than pre-tests. In addition, changes in work behavior and increased administrative efficiency are reflected in the use of computers in daily work. One of the program's sustainability strategies is the formation of the Village Digital Working Group (KKDD) which functions as a local digital literacy agent. The output of the activity in the form of training modules, operational guides, and activity documentation have been submitted to village partners. This activity proves the effectiveness of academic interventions in increasing village technological capacity and strengthening administrative governance. The results of this service also show the importance of collaboration between academics and the community in bridging the digital divide. This model can be replicated in other villages with similar challenges.